Potential of phytic acid extracted from rice bran as antioxidative compound and anti-proliferation agent in colon cancer cell line - Mohamed Shakrin, Norashareena (2013)
Phytic acid (IP6 or PA) which occurs at 9.5-14.5% in weight in rice bran has been reported to posses various significant health benefits including a potential as antioxidant and anticancer. It is a powerful inhibitor of iron mediated generation of hydroxyl radical (OH) that proposes may lower the incidence of colonic cancer. This research was done to study the potential of PA extracted from rice bran as an antioxidant agent and as antiproliferative agent on colon cancer cell line, HT-29. For optimization of PA extraction from defatted rice bran, three types of acidic solution were used (hydrochloric acid, sulphuric acid and trichloroacetic acid) with different concentration, pH and time of extraction. Neutralization of the sample extract was then performed to formulate the sample to be applied for in vitro followed by the purification by Anion-Exchange chromatography. The isolation and quantitation of PA was done by using reverse-phase High Performance Liquid Chromatography (HPLC). Five methods were used to analyze the antioxidant activity of the rice bran PA and to compare its antioxidant activity with corn PA and butylated hydroxytoluene (BHT). For the assessment of cytotoxicity effect of PA on HT-29 colon cancer cell, MTS (3-4,5-dimethylthiazol-2-yl-5-3-carboxymethoxy phenyl-2-4-sulfophenyl-2H tetrazolium, inner salt assay was used. The conjugated of FITC (fluorescein isothiocyanate) and Annexin V was used to quantitate apoptotic cells on a single-basis by flow cytometry and the qualitative apoptosis assay by Tunel assay (microscopy). Results showed the highest amount of PA extract yielded (11.14mg/g) by using 5% of sulphuric acid in pH 0.6 for 30 minutes of extraction. For antioxidant assays, by u sing β -carotene bleaching method, the results for rice bran PA, corn PA and BHT are 93.075%±3.099, 92.550%±9.635 and 109.610%±4.238, respectively. Meanwhile, for FTC and TBA method, the results for rice bran PA, corn PA and BHT are (74.76%±0.05 and 40.05%±0.03), (74.89%±0.03 and 34.42%±0.09) and (86.02±0.05 and 64.30%±0.04) respectively. The order of ferric reducing effect power (FRAP value) was: corn PA (2.738 mM±0.013) > rice bran PA (2.107 mM±0.006) > BHT (1.567 mM±0.039). DPPH assay indicates that PA has low radical scavenging effect, which was in the range of 10.1 to 41.0% merely. The antioxidant activities of both PA measured by all methods are not significantly different between each other. For cytotoxicity assays, rice bran PA and corn PA produced a 50% net of inhibition growth (IC50) at the dose of 25.3±5.23 μg/mL and 35.2±3.11 μg/mL respectively. The IC50 value of rice bran PA is significantly different with corn PA. Result from the quantitative apoptosis assay showed at the IC50 concentration, the percentage of treated cells undergone early apoptosis and late apoptosis for rice bran PA is 18.54%±1.55 and 38.41%±1.78, while the corn PA is 1.7%±0.10 and 4.35%±0.26 respectively. The percentage of total apoptotic cells at IC50 concentration for the rice bran PA is higher (56.9%) compared to corn PA (6.1%). The results exposed that both samples induced the exposure of phophatidylserine on outer cell membrane detected by using Annexin V-FITC. Conversely, the qualitative apoptosis assay by Tunel assay are demonstrated that none of the both phytic acid induced cells emits green fluorescence indicated that none of the treated cells underwent apoptosis. Though, since the results from both quantitative and qualitative apoptosis assays were not comparable to each other, further assessment is needed. In conclusion, our findings showed that PA extracted from rice bran posses the anti proliferative effect on colon cancer cell line (HT-29). One possible mechanism is by antioxidant activity that showed high in PA extract as demonstrated in our findings. The PA showed its strong characteristic of antioxidant activity by minimizing the coupled oxidation of linoleic acid (free radical) and beta carotene in β-Carotene bleaching assay, capability as ferric reducing power in FRAP assay and as a hydrogen peroxide scavenger at the initial stage of lipid oxidation in FTC assay but not as a free radical scavenger in DPPH assay.